2018
DOI: 10.3847/1538-4357/aae394
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Star Formation on Subkiloparsec Scales in the High-redshift Galaxy SDP.11 Using Gravitational Lensing*

Abstract: We investigate the properties of the interstellar medium, star formation, and the current-day stellar population in the strongly-lensed star-forming galaxy H-ATLAS J091043.1-000321 (SDP.11), at z = 1.7830, using new Herschel and ALMA observations of far-infrared fine-structure lines of carbon, oxygen and nitrogen. We report detections of the [O iii] 52 µm, [N iii] 57 µm, and [O i] 63 µm lines from Herschel/PACS, and present high-resolution imaging of the [C ii] 158 µm line, and underlying continuum, using ALMA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 67 publications
5
14
0
Order By: Relevance
“…Although the [C ii] luminosity increases in the FIR-bright region of the source, at the position of the peak FIR surface brightness, the [C ii] emission shows a significant drop, indicating an extremely low [C ii]/FIR ratio. A similar drop in [C ii]/FIR ratio at the continuum peak was recently found in a z = 1.7 lensed DSFG SDP.11 (Lamarche et al 2018), in which the regions with the highest ΣSFR are essentially undetected in the [C ii] line emission. We will address the [C ii]/FIR ratio in SDP.81 in more detail in Section 4.3. , and (10-9) line emission (units mJy km s −1 kpc −2 ), and ALMA Bands 6, 7 and 8 continuum (units mJy kpc −2 ), with associated 1σ uncertainty maps; the CO(5-4) and CO(8-7) data are adopted from R15b.…”
Section: [Cii] Emissionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although the [C ii] luminosity increases in the FIR-bright region of the source, at the position of the peak FIR surface brightness, the [C ii] emission shows a significant drop, indicating an extremely low [C ii]/FIR ratio. A similar drop in [C ii]/FIR ratio at the continuum peak was recently found in a z = 1.7 lensed DSFG SDP.11 (Lamarche et al 2018), in which the regions with the highest ΣSFR are essentially undetected in the [C ii] line emission. We will address the [C ii]/FIR ratio in SDP.81 in more detail in Section 4.3. , and (10-9) line emission (units mJy km s −1 kpc −2 ), and ALMA Bands 6, 7 and 8 continuum (units mJy kpc −2 ), with associated 1σ uncertainty maps; the CO(5-4) and CO(8-7) data are adopted from R15b.…”
Section: [Cii] Emissionsupporting
confidence: 78%
“…While this might partially stem from systematic uncertainties in ΣSFR estimates and the varying fraction of the [C ii] emission from ionized gas (c.f., Díaz-Santos et al 2017), the observed [C ii]/FIR dispersion is likely due to the intrinsic scatter in galactic properties, such as gas and dust conditions. From the SDP.81 data, we estimate the best-fitting log ΣSFR-log([C ii]/FIR) slope of −0.75 ± 0.01, using orthogonal distance regression, similar to the slope of −0.7 derived byLamarche et al (2018) for SDP.11. This is much steeper than theSmith et al (2017) trend (−0.21 ± 0.03).…”
mentioning
confidence: 99%
“…Although their observation suffered from a very sparse uv-plane coverage, they found the resolved [C II]-FIR deficit at z ∼4.5 to follow the trend seen in local galaxies. Similarly, high-resolution ALMA observations of [C II]/FIR deficit in two strongly lensed galaxies at z=1.7 and 5.6 were recently presented by Lamarche et al (2018) and Litke et al (2018), respectively, showing a pronounced [C II]/FIR deficit (10 −4 − 10 −3 ) on (sub)kpc scales.…”
Section: Introductionsupporting
confidence: 75%
“…The 602 − 720 GHz band 9 receivers can observe this line in galaxies during the Epoch of Reionization at z > ∼ 6, and have been used to study the [CII]158µm line in lower redshift galaxies (e.g. Schaerer et al 2015;Zanella et al 2018;Lamarche et al 2018).…”
Section: Discussionmentioning
confidence: 99%